Health literacy in Beijing: an assessment of adults’ knowledge and skills regarding communicable diseases - Zhang, Daitao (BMC Public Health, 2015)
BACKGROUND: There have been a number of studies conducted to date looking at the issue of health literacy, but none have been conducted in Beijing, China. The aim of this study was to evaluate the communicable diseases health literacy (CDHL) levels of Beijing residents towards three key areas: knowledge, adoption of preventative measures/behaviours, and health skills. METHODS: A structured survey was undertaken with Beijing residents aged ≥18 years. A multistage stratified sampling approach was used to identify and recruit residents. Participants were excluded if they were foreigners, residents of Hong Kong, Macau or Taiwan, or were unable to communicate in Mandarin. RESULTS: The questionnaire was completed by 11052 participants, with a moderate accuracy rate (average: 61.3 %) and a good discrimination level (average: 0.428). Cronbach’s alpha was 0.748. The items were grouped into three subscales representing knowledge, adoption of preventative measures and behaviours, and health skills. Correlations of the subscales and the Total Score is significant (P < 0.01), and all the three subscales correlate strongly with the Total Score The mean CDHL score of Beijing inhabitants was 15.28. The percentage of those who were identified as having adequate CDHL was 41 %. CONCLUSIONS: The total CDHL level of residents in Beijing was relatively low, particularly in those residing in the suburbs, those above 60 years of age, manual workers, and the illiterates. Gender, age-group, level of education, occupation, self-reported health status and region were all shown to be significantly predictive of CDHL. It is important that more resources are dedicated to improving the CDHL in Beijing, given the risk of emerging and re-emerging infectious diseases in the region.